Efficacy and safety evaluation of frontline immunotherapy combinations in advanced esophageal squamous cell carcinoma: a network meta-analysis highlighting the value of PD-L1 expression positivity scores - Chen, Wei; Cao, Keming; Zhang, Lili; Zhao, Xingyu; Chen, Bixiao; Li, Wei; Shang, Rongguo; Sun, Lichaoyue; Jiang, Ze; Wang, Jingxin; Xue, Wenxin (Frontiers in Immunology, 2024)
Introduction：The systematic review and network meta-analysis (NMA) consolidate all relevant randomized controlled trials (RCTs) related to initial immunotherapy treatments for advanced esophageal squamous cell carcinoma (ESCC). Our goal is to thoroughly assess the effectiveness and safety of various immunotherapy methods, focusing on overall survival (OS) and progression-free survival (PFS) among patients with advanced ESCC positive for PD-L1. Methods：We conducted a systematic search of the PubMed, Embase, Cochrane Library, and Web of Science databases, covering all records from their inception until January 22, 2024. The inclusion criteria targeted patients with advanced ESCC undergoing first-line immunotherapy or chemotherapy, limiting the study selection to randomized controlled trials (RCTs) exclusively. The study upholds the values of openness, originality, and dependability, as evidenced by its enrollment in the Prospective Register of Systematic Reviews (CRD42024504992). Results： Our analysis encompasses 7 RCTs, totaling 4688 patients, and evaluates 8 distinct immunotherapy combinations. In advanced ESCC patients irrespective of PD-L1 expression, both sintilimab-chemotherapy and toripalimab-chemotherapy regimens demonstrated comparable OS benefits (HR=0.92, 95% CI: 0.64-1.33). The most pronounced PFS advantages were seen with sintilimab-chemotherapy and camrelizumab-chemotherapy as compared to standard chemotherapy (HR=0.56, 95% CI: 0.46-0.58). Notably, camrelizumab-chemotherapy (HR=0.83, 95% CI: 0.59-1.16) and nivolumab-ipilimumab (HR=0.84, 95% CI: 0.60-1.17) demonstrated significant safety profiles over chemotherapy alone. Subgroup analysis based on PD-L1 expression revealed nivolumab-chemotherapy to yield the highest OS benefit (HR=0.54, 95% CI: 0.37-0.79) in ESCC patients with PD-L1 expression ≥1%. Furthermore, camrelizumab-chemotherapy (HR=0.51, 95% CI: 0.39-0.67) exhibited superior PFS benefits. Among patients with PD-L1 expression ≥10%, camrelizumab-chemotherapy (HR=0.52, 95% CI: 0.35-0.78) emerged as the most efficacious in improving OS, while serplulimab-chemotherapy (HR=0.48, 95% CI: 0.34-0.68) was associated with the longest PFS benefit. Conclusion：The integration of immune checkpoint inhibitors (ICIs) with chemotherapy appears to significantly enhance survival outcomes in patients with advanced ESCC compared to chemotherapy alone. Sintilimab-chemotherapy is potentially the optimal regimen for patients without PD-L1 expression. In contrast, nivolumab-chemotherapy and camrelizumab-chemotherapy are likely to offer the best OS and PFS benefits, respectively, in patients with PD-L1 expression ≥1%. Since most of the patients in this study originated from Asia, the above findings are more applicable to the Asian population.